2006
DOI: 10.1007/s10640-006-9012-4
|View full text |Cite
|
Sign up to set email alerts
|

An Enforcement-Coalition Model: Fishermen and Authorities Forming Coalitions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…In doing so we provide insights in how the stability of the PNA as a 'new fisheries sub-region' adjacent to the wider WCPFC is maintained. Our empirical application supports the notion that players are better off under full cooperation in the long term (Kronbak et al 2006), but full cooperation only appears to be more beneficial in the absence of free rider incentives derived from (pre)existing access agreements. As a result incomplete compliance emerges as the more rational option in the short term.…”
Section: Implications For Fisheries Regionalismsupporting
confidence: 74%
“…In doing so we provide insights in how the stability of the PNA as a 'new fisheries sub-region' adjacent to the wider WCPFC is maintained. Our empirical application supports the notion that players are better off under full cooperation in the long term (Kronbak et al 2006), but full cooperation only appears to be more beneficial in the absence of free rider incentives derived from (pre)existing access agreements. As a result incomplete compliance emerges as the more rational option in the short term.…”
Section: Implications For Fisheries Regionalismsupporting
confidence: 74%
“…In the final 2 stages, fishers choose their coalition structure and then optimize their effort to maximize profit. Their analysis has interesting implications for the institutional structures of governance (centralized versus decentralized) on compliance behavior of fishers (Kronbak & Lindroos 2006). Specifically with regard to the costs of enforcement, they found that cooperation among those setting the rules leads to higher compliance among fishers.…”
Section: Leader−follower Gamesmentioning
confidence: 99%
“…This follows the approach taken by Charles et al (1999), although those authors did not explicitly describe their model as a leader−follower game, and the work of Kronbak & Lindroos (2006). In the first analysis, the authors compared an unregulated fishery with a fishery regulated by input and output controls, as initiated by the leader, with regulation including a probability of detecting illegal fishing and a penalty function applied to illegal fishers (the followers; Charles et al 1999), similar to that described by Sutinen & Andersen (1985).…”
Section: Leader−follower Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…2014;Miller et al 2014), gained prominence in the management of transboundary fisheries in the 1970s in response to increasing depletion of the world's fisheries resources (Tsamenyi et al 2001). Today, fisheries regionalism involves cooperation among states to develop policies, mobilise resources and execute relevant activities with appropriate degrees of integration (Hughes 2005;Hegland et al 2012). In complex environmental and political 'seascapes' like the Western and Central Pacific Ocean (WCPO), regional and sub-regional organisations have become the cornerstone of economic and social development of Pacific Island states, strengthening their position in the international policy arena that addresses trade, conflicts and transboundary marine resources such as tuna.…”
Section: Introductionmentioning
confidence: 99%